DESIGN AND IMPLEMENTATION OF MICROCONTROLLER-BASED CONTROLLING OF POWER FACTOR USING CAPACITOR BANKS WITH LOAD MONITORING - Hanif, A.; Rashid, M.; Ali, M. (The Nucleus, 2012)
In this research work, an automatic power factor correction (APFC) technique is presented to improve power factor of industrial loads to the desired value. Power factor is corrected to provide relief to utility by supplying required reactive power demand of load locally. The improvement of power factor of industrial customer will reduce customer monthly bill as well as will escape from financial penalty being imposed by utility owing to his low power factor. Different power factor correction (PFC) techniques exists, however we have proposed a new scheme of PFC using PIC microcontroller (18F452) chip. A microcontroller based algorithm is developed to measure power factor of load and examine the similarities or differences with the set referenced value of power factor to switch in required value of capacitors to correct the power factor of load to desired value. The developed scheme in perspective of controlling the power factor has a main advantage of choosing the direct value of capacitor that is needed to correct the necessitate amount of reactive power in order to cater the current utilization by the load. The prevailed results have affirmed that the developed scheme is able to yield a desirable power factor and can be furthermore pursued in practical applications.